Effectiveness of Feedback Using Motor Models on Free Throw Accuracy and Retention Rate among Female Students - Malik Jamal Abd Naser (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
This study aim to examines effectiveness concerning feedback based upon motor model inside of improving free throw accuracy inside of basketball plus its impact upon retention concerning skill among female student. Significance concerning this research lie inside of essential role concerning feedback inside of motor learning, particular when supported by way of accurate performance model that help learner to builds clear mental representation concerning movement execution.Experimental design were employed, involving sample concerning female student random assigned into two group. Experimental group receive feedback supported by way of motor model, including video demonstration concerning ideal plus corrected performance, while control group follow traditional instruction relying primary upon verbal explanation. Post-test were then administered to measures improvement, along alongside delayed retention test to evaluates persistence concerning learning over time. Result show statistical significant difference inside of favor concerning experimental group inside of both post-test plus retention outcome. This indicate that motor model-based feedback effective enhance performance plus support long-term skill retention. Addition, student exposed for motor model demonstrate greater ability to recognizes plus corrects error plus show deeper understanding concerning correct technique.Study recommend integrating motor modeling strategy plus technology-based feedback into sport education to accelerates learning plus improves outcome across educational context.